Latihan Permainan Katak dan Bangau Untuk Meningkatkan Kebugaran Jasmani Siswa Sekolah Dasar - Ruswan, Acep; Fajrussalam, Hisny; Wulan, Neneng Sri (CV. Creative Tugu Pena, 2022)
This research is motivated by the importance of physical fitness in elementary school students. This study aims to determine the effect of playing frog and stork in improving the physical fitness of elementary school students. To achieve this goal, a test instrument regarding physical fitness is needed which will be compiled and then tested on elementary school students. Physical fitness comes from four aspects that are assessed, namely (1) Shuttles Run Test 4x10 meters (in seconds), (2) Throwing and Catching Balls 1 meter to the wall, (3) Stork Stand Positional Balance Test (in minutes), and (in minutes) 4) 30 Meters Sprint (in seconds). This research took place at SD Negeri 2 Sindangkasih, Purwakarta District, Purwakarta Regency. The results showed that the physical fitness of elementary school students increased after the frog and stork game exercise Keywords: Improving Physical Fitness, Inportant Physical Fitness, Physical Fitness